Spasimir Domaradzki Tax policies in Poland, Slovakia, and Bulgaria: sitting on a ticking bomb or catching up with the West (Economic and Political Thought, 2017)
This paper conducts a comparative review of Bulgaria, Slovakia andPoland’s taxation system performance in pursuit of the question whetherthe flat tax system was able to meet the hopes reposed in it. The threecountries were selected because they nominally contain different taxationsystems: Poland has a progressive one; Slovakia has a flat tax while retainingsome elements of progressive taxation; whereas Bulgaria has the most radicalflat tax system in the region. Furthermore, after a quarter of a century theireconomic and tax experience does not correspond with the expectationsof the flat tax dogma. The research argues that the question whether thetaxation system in the region is flat or not is of secondary importance,despite the fact that all the tax systems in their essence aim to performin a very similar ‘flattened’ taxation pattern. Secondly, that the quest forforeign direct investments cannot be pursued blindly and uncritically, sincethe three countries’ experience reveals alternative and most importantly,not only positive achievements. Finally, the paper argues that the currentperformance of the three countries’ taxation systems does not correspondwith the expectations that the flat tax system will resolve the internaloperational difficulties such as high compliance gaps, tax evasion and weaktax administration. Having in mind that after a quarter of a century the threecountries reached different levels of economic development, the questionremains whether the current taxation systems are still relevant or they havelost their appropriateness. Poland and Slovakia are approaching the challengeof a ‘middle income trap’, whereas Bulgaria still needs to ‘catch up’. Thus,the former two should reconsider the current pressuring weaknesses of theirtaxation systems, whereas the latter should reassess its approach towardsforeign direct investments and reconsider the direction of its tax policy.